Sesamol Ameliorates Renal Injury-Mediated Atherosclerosis via Inhibition of Oxidative Stress/IKKα/p53 - Jie-Sian Wang; Ping-Hsuan Tsai; Kuo-Feng Tseng; Fang-Yu Chen; Wen-Chin Yang; Ming-Yi Shen (MDPI AG, 2021)
Patients with chronic kidney disease (CKD) are at an increased risk of premature death due to the development of cardiovascular disease (CVD) owing to atherosclerosis-mediated cardiovascular events. However, the mechanisms linking CKD and CVD are clear, and the current treatments for high-risk groups are limited. In this study, we aimed to examine the effects of sesamol, a natural compound extracted from sesame oil, on the development of atherosclerosis in a rodent CKD model, and reactive oxygen species-induced oxidative damage in an endothelial cell model. ApoE-/- mice were subjected to 5/6 nephrectomy (5/6 Nx) and administered sesamol for 8 weeks. Compared with the sham group, the 5/6 Nx ApoE-/- mice showed a significant increase in malondialdehyde levels and Oil Red O staining patterns, which significantly decreased following sesamol administration. Sesamol suppressed H2O2-induced expression of phospho-IKKα, p53, and caspase-3. Our results highlight the protective role of sesamol in renal injury-associated atherosclerosis and the pathological importance of oxidative stress burden in CKD-CVD interaction.